5-Aza-2′-deoxycytidine, a DNA methylation inhibitor, induces cytotoxicity, cell cycle dynamics and alters expression of DNA methyltransferase 1 and 3A in mouse hippocampus-derived neuronal HT22 cells. Issue 22 (17th November 2017) - Yang, Jing; Tian, Xiaoli; Yang, Jie; Cui, Junhe; Jiang, Shuyuan; Shi, Rui; Liu, You; Liu, Xiaolei; Xu, Wenqiang; Xie, Wei; Jia, Xiaoe; Bade, Rengui; et al.
ABSTRACT: Epigenetic processes such as DNA methylation are essential for processes of gene expression in normal mammalian development. DNA methyltransferases (DNMT) are responsible for initiating and maintaining DNA methylation. It is known that 5-Aza-CdR, an inhibitor of DNMT induces cytotoxicity by reducing DNMT activity in various tumor cell lines. However, disturbances in neuronal DNA methylation may also play a role in altered brain functions. Thus, it was of interest to determine whether alterations in DNA methylation might be associated with neuronal functions by using 5-Aza-CdR, on mouse hippocampus-derived neuronal HT22 cell line. In particular, the aim of this study was to investigate the effects of 5-Aza-CdR on cell growth inhibition, cell cycle arrest, apoptosis as well as the expression levels of DNMT in HT22 cells. HT22 cells were incubated with 5 or 20 μmol/L 5-Aza-CdR for 24 h. Data showed that 5-Aza-CdR at both concentrations significantly inhibited proliferation of HT22 cells and exacerbated cytoplasmic vacuolization. Flow cytometry analysis demonstrated that 5-Aza-CdR treatment at both concentrations decreased early apoptosis but enhanced late apoptosis. Cell cycle analysis illustrated that 5-Aza-CdR treatment induced S phase arrest. Further, incubation with 5-Aza-CdR produced a down-regulation in expression of mRNA and protein DNMT1 and 3A but no marked changes were noted in DNMT 3B and p21 expression. In addition, DNMT1 activity was significantly decreased at both 5-Aza-CdR concentrations. Evidence indicates that 5-Aza-CdR induced cytotoxicity was associated with altered mRNA and protein expression of DNMT 1 and 3A associated with reduced DNMT1 activity in HT22 cells which might affect brain functions.